Talent retention onboarding proposal in a manufacturing company in the State of Mexico - Guardado Lopez, Sinuhe Carlos (2023)
This article presents the problem of a manufacturing company established in Estado de Mexico, which exhibits higher levels of turnover than what is projected annually by the company's management, specifically in the Operations and Quality department. A study was carried out jointly with the organization's Human Resources department and with the Operations and Quality area, to determine, through an Ishikawa analysis, the cause and the most viable solution to reduce staff turnover, who joined the company. It is important to indicate that some data has been synthesized and others have been omitted for reasons of company confidentiality. In this study, it is concluded that an onboarding program is the most feasible to reduce the turnover of new personnel hired in the Operations and Quality department.